Comparing the effectiveness of Chinese patent medicines containing red yeast rice on hyperlipidaemia: A network meta‐analysis of randomized controlled trials. Issue 1 (11th November 2021) - Xu, Guiqin; Lin, Mingxin; Dai, Xueli; Hu, Jingqing
Abstract: Introduction: The purpose of this study was to evaluate the therapeutic effectiveness of Chinese patent medicines containing red yeast rice for the treatment of hyperlipidaemia. Methods: Relevant literature published until 13 August 2021, was retrieved from six electronic databases. Randomized clinical trials of Chinese patent medicines containing red yeast rice in patients with hyperlipidaemia were included in the review. Network meta‐analysis was performed using Stata 13.1 software. Methodological quality was assessed using the Cochrane risk of bias tool. The surface under the cumulative ranking (SUCRA) curve probability values were used to rank the treatments. Results: This study included 47 trials involving 4824 subjects. In terms of reduced total cholesterol levels, Xuezhikang (SUCRA: 84.5%) had the highest probability of being the most effective formulation, with Simvastatin (66.4%) and Zhibitai (65.4%) ranked second and third, respectively. Xuezhikang also had the highest probability of reducing low‐density lipoprotein cholesterol levels to the greatest extent (SUCRA: 82.6%) with Simvastatin (SUCRA: 74.9%) and Zhibituo (SUCRA: 52.8%) being the second and third choices, respectively. For reduced triglyceride levels, Zhibituo (SUCRA: 80.2%) exhibited the highest probability of being the most effective, with Xuezhikang (SUCRA: 63.4%) and Simvastatin (SUCRA: 57.6%) in second and third places, respectively. Finally, in terms of improving high‐density lipoprotein cholesterol levels, Zhibituo (SUCRA: 90.1%) had the highest probability of being the most effective, with Simvastatin (SUCRA: 82.1%) and Xuezhikang (SUCRA: 51.1%) ranked second and third, respectively. Conclusions: Xuezhikang was found to have the highest probability of being the most effective formulation for reducing total cholesterol and low‐density lipoprotein cholesterol levels, while Zhibituo had the highest probability of being the most effective for controlling triglyceride and high‐density lipoprotein cholesterol levels. The studies included in the review exhibited certain limitations and, therefore, more rigorously designed studies should be performed. Trial registration: INPLASY registration number: INPLASY202130017. Abstract : The purpose of the present study was to evaluate the therapeutic effectiveness of Chinese patent medicines containing red yeast rice for the treatment of hyperlipidaemia. Xuezhikang was found to have the highest probability of being the most effective formulation for reducing total cholesterol and low‐density lipoprotein cholesterol levels, while Zhibituo had the highest probability of being most effective for controlling triglyceride levels and high‐density lipoprotein cholesterol levels. The studies included in the review exhibited a number of limitations, and therefore, more rigorously designed studies should be performed.